Productive and reproductive performances of Brown Bengal goat (Hilly goat) at research farm level (Asian Journal of Medical and Biological Research, 2016)
A nucleus-breeding flock of selected Brown Bengal goat was established in the Bangladesh Livestock Research Institute (BLRI), Regional Station, Naikhongchari, Bandarban, with the objective of characterization, conservation and improvement of the breed. A total of 69 does of different generations (Foundation = 07, Generation one = 32, Generation two = 23 and Generation three = 07.) and 07 bucks (All were first generation) were used to study the genetic parameters of Brown Bengal goat on productive and reproductive traits. The studied Animals were bred naturally. Goats were reared under semi-intensive management system in which goats were browsing in nature and allowed to graze in field as well as mounting in hills. All goats were housed in a plastic made floor house and allowed to graze 6-8 hours in a day and concentrate was offered twice daily during morning and evening at the rate of 1% of their body weight per day. The adult body weight of hilly goat was 20.95 kg. The phenotypic characteristics like the face, horn, ear and udder length were 15.56, 7.18, 12.19 and 12.67 cm respectively. On the other hand the hearth girth, front leg, hind leg and body length were 61.51, 46.8, 49.48 and 55.24 cm respectively. The gestation length, kidding to first heat, kidding to conception and kidding interval were 148.52 ± 1.06, 33.48 ± 2.85, 33.40 ± 1.98 and 176.86 ± 1.98 days, respectively. According to parity the GL, AFH, KC and KI were not followed trends up to 3rd parity but kid birth weight was increasing trends with increasing parity up to fifth. The birth weight of male kid (1.25 ± 0.25 kg) was higher than that of female kid (1.13± 0.27 kg). The highest birth weight (1.24±0.02 kg) was found in single birth. According to litter size the birth weight of single kid (1.24 ± 0.01 kg) stood first followed by twine (1.20 ± 0.01), triplet (1.1±0.03 kg) and quadruplet kids (0.93±0.08 kg). . The productive and reproductive performances of brown Bengal goat were not affected by parity. Birth weights of kids were significantly varied with birth type.Asian J. Med. Biol. Res. September 2016, 2(3): 477-482